2017
DOI: 10.1080/15476286.2017.1341020
|View full text |Cite
|
Sign up to set email alerts
|

dRNA-seq transcriptional profiling of the FK506 biosynthetic gene cluster in Streptomyces tsukubaensis NRRL18488 and general analysis of the transcriptome

Abstract: FK506 (tacrolimus) is a valuable immunosuppressant produced by several Streptomyces strains. In the genome of the wild type producer Streptomyces tsukubaensis NRRL18488, FK506 biosynthesis is encoded by a gene cluster that spans 83.5 (kb). A whole transcriptome differential shotgun sequencing (dRNA-seq) of S. tsukubaensis was performed to analyze transcription at 2 different time points; before and during active FK506 production. In total, 8,914 transcription start sites were identified in either condition, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 51 publications
(81 reference statements)
3
10
0
Order By: Relevance
“…These results are supported by the EMSAs performed with the FkbN-DNA binding domain in S. tsukubaensis L19 by Zhang and coworkers [ 75 ], who reported FkbN binding to the promoter regions of the same six transcriptional units and identified two new ones corresponding to allNPOS and allM . More recently, differential RNA-seq (dRNA-seq) transcriptional profiling has been performed in S. tsukubaensis by Bauer and coworkers [ 39 ], who identified 9 transcriptional units that are in good agreement with previous studies ( Figure 2 ). The main finding is that allOS and allNP are transcribed as independent mRNAs [ 39 ].…”
Section: Transcriptional Regulators and Recent Insights Through Trsupporting
confidence: 78%
See 2 more Smart Citations
“…These results are supported by the EMSAs performed with the FkbN-DNA binding domain in S. tsukubaensis L19 by Zhang and coworkers [ 75 ], who reported FkbN binding to the promoter regions of the same six transcriptional units and identified two new ones corresponding to allNPOS and allM . More recently, differential RNA-seq (dRNA-seq) transcriptional profiling has been performed in S. tsukubaensis by Bauer and coworkers [ 39 ], who identified 9 transcriptional units that are in good agreement with previous studies ( Figure 2 ). The main finding is that allOS and allNP are transcribed as independent mRNAs [ 39 ].…”
Section: Transcriptional Regulators and Recent Insights Through Trsupporting
confidence: 78%
“…More recently, differential RNA-seq (dRNA-seq) transcriptional profiling has been performed in S. tsukubaensis by Bauer and coworkers [ 39 ], who identified 9 transcriptional units that are in good agreement with previous studies ( Figure 2 ). The main finding is that allOS and allNP are transcribed as independent mRNAs [ 39 ].…”
Section: Transcriptional Regulators and Recent Insights Through Trsupporting
confidence: 78%
See 1 more Smart Citation
“…In fact, Zheng et al ( 2011 ) provided some insights into genes encoding leaderless mRNA in prokaryotes by a bioinformatics method, revealing that leaderless mRNA are widely spread in a variety of bacteria, especially in phyla Actinobacteria and Deinococcus - Thermus . Moreover, previous experimental studies have also revealed a high proportion of leaderless mRNA in some prokaryotes especially in Archaea (Torarinsson et al, 2005 ; Babski et al, 2016 ; Bauer et al, 2017 ).…”
Section: Discussionmentioning
confidence: 92%
“…[17] Direct digital extraction of chemical shifts from the raw data [18] will push the protocol closer to native computational interrogation. This in turn will expedite the growth of the database,which we anticipate will eventually be able to assign the structural features of each carbon and proton within ag iven molecule.W hile structural assignment is ak ey facet of the drug discovery process,t he ability to search through molecular data one atom at at ime offers an ew perspective that can enable this system to operate through aconventional online portal, one that ideally will be united with biosynthetic genome mining tools [19] such as antiSMASH, [20] as well as proteomic [21] and transcriptomic [22] data. Ultimately,i tw ill be interesting to understand the correlation between structural novelty and its role in inducing novel biological activity,p erhaps done best one atom at atime.…”
mentioning
confidence: 99%